An Energy Efficient Clustering based Optimal Routing Mechanism using IBMFO in Wireless Sensor Networks - S. Srinivasa Rao; K. Chenna Keshava Reddy (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Recently, the Wireless Sensor Networks (WSNs) are extensively used in many real-time applications due to their scalability, dynamicity, and mobility. Since, optimizing the energy consumption of nodes, and improving the lifetime of network are still remains the challenging tasks. In the conventional works, the different types energy efficient clustering and routing methodologies are developed for improving the networking operations and performance of WSN. However, it limits with the major problems of reduced speed of processing, increased complexity in algorithm design, inefficient QoS, and high average residual energy. Therefore, the proposed work objects to implement an advanced optimization based clustering and routing methodologies for ensuring the better lifetime, energy efficiency and QoS of WSN. Here, an Improved Butterfly Optimization (IBO) technique is deployed to optimally select the CHs based on the parameters of energy, distance, node degree, and centrality. Then, the best and energy efficient routing paths between the source and destination nodes are selected to establish the data transmission by using the Moth Flame Optimization (MFO) technique, which ensures the reliable and valid data routing in the network. During simulation, the performance of the proposed IBMFO technique is validated and compared by using various evaluation metrics.